Standards ISO 14001:2015 as The Basis for Green Innovation, Sustainable Development and Competitive Advantage: The Case of State Energy Company PT Pertamina (Persero) - Agus Santosa (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2020)
The Paris Agreement on climate change (2015) emphasizes among other priorities the importance of environmental innovation, including technical, technological, organizational, which has significant potential to minimize the negative impact of the industry on the environment. In addition, customers, consumers and shareholders increasingly care and demand the same from our activities, our products and the services they consume. They expect companies to comply with environmental standards and demonstrate our commitment to reduce environmental impacts in daily operations. The task of technology modernization and relevant organizations for various sectors of the national economy. Especially important for energy companies (PERTAMINA). The author analyzes new environmental management tools, which were introduced in the ISO 140001: 2015 standard and outlines some recommendations for improvement in the context of PERTAMINA’s conditions. The author also analyzes how to align these requirements with the upcoming transition of energy companies to the best available technology, which is basically a form of increasing technical and technological innovation. To ensure the successful implementation of these innovations, it is necessary to use, in addition to environmental management standards, a mix of environmental policy instruments, including what is referred to as green finance. It may be a challenge, but it is also an opportunity for us to show our environmental responsibility, stand out from the competition and show our existing customers and potential evidence of our commitment.